Sentencing in light of collateral consequences: Does age matter?. (November 2017) - Ryon, Stephanie Bontrager; Chiricos, Ted; Siennick, Sonja E.; Barrick, Kelle; Bales, William
Abstract: Purpose: Most sentencing studies control for offender age, but we know little about how age influences alternative sentencing outcomes, especially those that can mitigate the collateral consequences of conviction. Theories predict varying effects of age based on the focal concerns issues of blameworthiness, community protection, and practical constraints, and prior findings on main and interactive age effects are mixed. Methods: This study draws on Florida sentencing data ( N  = 240, 844) spanning 2000–2006 to examine how offender age influences the avoidance of a felony label by the withholding of adjudication, for defendants convicted of a felony and sentenced to probation. Logistic regression and heterogeneous choice models are used to examine the effects of age on the predicted log-odds of having adjudication withheld. Results: The results demonstrate a curvilinear age relationship with adjudication withheld, protecting youthful and, to a lesser extent, older offenders from felony labels. This non-linear relationship is robust to interactions with gender, race/ethnicity, and offense type, illustrating the importance of age and the need for additional research to examine its effects more fully. Conclusions: The evidence suggests that age plays an important role in decisions to utilize alternative sanctions in the criminal justice system. The youngest and oldest offenders benefit the most, while adults face the harshest consequences and are less likely for consideration of alternative sentencing options. These results hold important policy implications in light of criminogenic trajectories for youthful offenders, systems burdened with aging prisoner populations and theoretical perspectives on age, sentencing and collateral consequences. Highlights: The relationship between age and adjudication withheld, an intermediate sanction, is non-linear. The Youngest and Oldest offenders benefit the most from their age in the withholding of adjudication. The age benefit does not extend as much to minorities and adults, or those convicted of serious felony offenses such as homicide.